MINIMUM INVASIVITY OF IMPLANTATION TECHNIQUES, COMPARISON AND SELECTION CRITERIA - Isciuc Ioana; Lavinia Oarza; Ana Maria Balasca; Ioana Apetrei; Nicolae Coceanu; Roxana Pintilie; Forna Norina Consuela (Romanian Dental Association for Education, 2022)
Today's patients lead a busy and active lifestyle, and prolonged periods of convalescence are not acceptable for many. Therefore, the advent of minimally invasive surgery has promoted increased patient acceptance, which result from decreased morbidity associated with the minimally invasive surgery approaches. The present literature review focuses on the comparative aspects of flapped versus flapless implants in terms of their survival, marginal bone loss, soft-tissue parameters, and patient-centered outcomes. When the proper protocol is followed by experienced surgeons, no significant difference was observed in survival rate, marginal bone loss, and keratinized mucosal width between flapless and conventional flap technique. Although transgingival approach for implant placement is reported to significantly reduce the surgical time, increased patient comfort and acceptance, i.e. the patient centered outcomes such as postoperative pain, swelling, and visual analog score, are minimized. Hence, it is concluded that transgingival (flapless) implant placement technique is well accepted by the patient with potential outcomes as compared to the conventional implant placement approach. Transgingival (flapless) implant placement procedure is a minimally invasive surgical technique in which implant is placed without reflecting mucoperiosteal flap and hence the blood supply of bone is not hampered which is advantageous in many ways. An electronic search without time or language restrictions was undertaken in May 2022. Eligibility criteria included clinical human studies, either randomized or not.